Temperature dependent electron transport behavior of poly (methyl methacrylate)/silver functionalized reduced graphene oxide films - Asha, S. (AIP Conference Proceedings, 2018)
Poly (methyl methacrylate) (PMMA) and silver functionalized reduced graphene oxide film were prepared and were investigated using FTIR and Raman. Electron transport behavior of these samples, at low temperature were studied. The prepared film exhibited a temperature dependent electron transport, at higher temperatures Arrhenius-like temperature dependence of resistance was observed indicating band like electron transport with a small thermal activation energy. At further lower temperatures hopping mechanism of conduction was observed due to the presence of defects. The conduction due to band-like electron transport at higher temperature is attributed to the easier excitation of charge carriers to the conduction band, whereas at lower temperatures conduction occurs through hopping mechanism due to localized states around Fermi level in the presence of defects.

Temperature assisted reorganization of silver nanoparticles in free-standing, flexible chitosan functionalized reduced graphene oxide thick films: A potential SERS probe for folic acid sensing - Asha, S.; Ananth, A. Nimrodh; Jose, Sujin P.; Rajan, Michael Anjello Jothi (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2020)
Chitosan and silver functionalized free standing reduced graphene oxide (rGO) films were prepared using simple soak and dry strategy. Redistribution of silver aggregates on chitosan functionalized rGO films were observed by thermally annealing these films at 450 degrees C, in an inert atmosphere. The re-organization / redistribution of silver aggregates in the rGO films were studied using in-situ Raman scattering signals. The redistribution of silver particles occurs through melting of micron sized silver aggregates during annealing. The rearrangement of the micro-sized silver aggregates to spherical silver nanoparticle on chitosan functionalized rGO film, as a result of temperature was assisted through factors such as graphene surface ripple rearrangement and the denaturation of rGO surface interacting chitosan chains. These free-standing films with redistributed silver nanoparticles showed excellent surface enhanced Raman scattering (SERS) effect with enhanced Raman signals for folic acid sensing, showcasing its potentiality to be utilized as flexible SERS based sensors.
Keywords: Free-standing; graphene oxide; sensing; SERS; silver nanoparticles; Thick-films